2023
DOI: 10.1159/000529337
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Resilience of Older Adults with Cognitive Decline Requires a Multi-Level System Approach

Abstract: The concept of resilience, i.e., the capacity of a system to bounce back after a stressor, is gaining interest across many fields of science, policy and practice. To date, resilience research in people with cognitive decline has predominantly addressed the early stages of decline. We propose that: (1) resilience is a relevant concept in all stages of cognitive decline; and (2) a socioecological, multisystem perspective on resilience is required to advance understanding of, and care and support for people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Further research may consider how the model may support resilience of the wider networks in the environment around the person with dementia. 66 Understanding diversity in meaning of life prolongation as a care goal is important for the use both of this model and the white paper model that also included it. The usefulness of life prolongation as a goal of care should also be understood from the perspective of persons with dementia and their family to best serve their interests.…”
Section: Discussionmentioning
confidence: 99%
“…Further research may consider how the model may support resilience of the wider networks in the environment around the person with dementia. 66 Understanding diversity in meaning of life prolongation as a care goal is important for the use both of this model and the white paper model that also included it. The usefulness of life prolongation as a goal of care should also be understood from the perspective of persons with dementia and their family to best serve their interests.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional brain-aging research has categorized brain aging into distinct categories: resilient brain aging (RBA) [10][11][12], normal brain aging, and accelerated brain aging (ABA), occasionally referred to as advanced brain aging [13,14]. Such studies have revealed that RBA is associated with a greater resistance to the risk of neurodegenerative diseases like Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of neuroscientific research, brain aging in cognitively normal individuals has been meticulously classified to include resilient brain aging (RBA) [5][6][7], normal brain aging, and accelerated brain aging (ABA) [5,8,9], sometimes colloquially termed advanced brain aging. RBA is a concept that describes the ability of certain individuals to maintain neural integrity relatively well as they age.…”
Section: Introductionmentioning
confidence: 99%